PERLINDUNGAN KONSUMEN TERHADAP PENERAPAN UKURAN TAKARAN TIMBANGAN DAN PERLENGKAPNNYA BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 1981 TENTANG METROLOGI LEGAL PADA PEDAGANG PASAR LIMAPULUH DI KOTA PEKANBARU - Ibnu Rahmat Dio; Mardalena Hanifah; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Low awareness and knowledge society as consumers, make the consumer as the object of business activity for businesses to obtain maximize profits in various ways that are not selling well, including the manipulation of prices, selling a defective product as well as reducing measures and weights. The number of consumers who are victims of the reduction measures and weights by traders require governments to provide monitoring and protection. One of the government agencies that play an active role in overseeing businesses and provide consumer protection is the Department of Trade and Industry, through the agency of Legal Metrology Unit oversees a range of activities including business operators regarding the implementation of measures and weights traditional market traders. Consumer protection and supervision to prevent fraud by businesses to the public as consumers.The problems discussed in this thesis is how the protection of consumers conducted Department of Industry and Trade of Pekanbaru to the adoption by the market sellers UTTP Limapuluh and whether the constraints and how the efforts of the Department of Industry and Trade of the City of Pekanbaru to optimize consumer protection for the future.The method used in this research is a kind of sociological research. The nature of this research is descriptive and research done on Limapuluh Market and the Office of Industry and Trade of the City of Pekanbaru. Samples taken in this study as many as 46 people by using purposive sampling method. Source data in this study was obtained through primary and secondary data. Data collection techniques used is through questionnaires, interviews, and literature studies. While data analysis technique using qualitative descriptive analysis.The results showed that the efforts of the Department of Trade and Industry in providing consumer protection related to the implementation of tera UTTP is re-scheduled each year and provide counseling how to do good and honest trade related to the implementation of measures and weights to the market traders Limapuluh Pekanbaru. Constraints experienced by the Department of Industry and Trade is a lack of initiative merchants to make re tera and various characters trader adds to the difficulty to provide an appeal related to fairness in trade transactions. Effort will be made of Industry and Commerce for the future is to provide a measuring post repeated by providing a single scale for each of the traditional market that can be used by communities to reconsider groceries.Keywords: Consumer Protection, UTTP, Traders, Market